RELATIONSHIP OF AGE, REPETITIVE ACTIVITIES, WORK POSTURE AND WORKING PERIOD WITH SUBJECTIVE COMPLAINTS OF MUSCULOSKELETAL DISORDERS (MSDS) IN LAUNDRY WORKERS IN JAMBI CITY IN 2022 - Dwi Fuja Netasya; Eko Mirsiyanto; Novi Berliana (Bajang Institute, 2023)
Complaints in the musculoskeletal system are complaints that a person feels in their skeletal muscles, starting from mild to severe complaints. The purpose of this study is to relationship age, repetitive activities, work posture and length of work to MSDs complaints experienced in Laundry workers in Jambi City in 2022. This type of research is quantitative research with a cross-sectional approach. This study was conducted at a laundry business in Jambi City with a sample of 42 workers. Sampling using the total sampling technique. Primary data were taken using NBM questionnaires, interviews, measurements with REBA and video/stopwatches. The data were analyzed univariately and bivariately using the chi-square test. As many as 11.9% of respondents experienced musculoskeletal complaints in the high category, 52.4% of respondents experienced a risky age, 31% of respondents experienced repetitive activity, 42.9% of respondents with moderate work posture and 7.1% had a long working life. The bivariate results showed that there was a relationship between age and MSDs complaints (p-value 0.023), there was no relationship between repeated activities and MSDs complaints (p-value 0.134), there was no relationship between work posture and MSDs complaints (p-value 0.074) and no contact between length of service and MSDs complaints (p-value 0.509).